PROSES PERUBAHAN PROSEDUR KEUANGAN PADA SMK MAHAPUTRA KABUPATEN BANDUNG - Deni Hamdani; Sudi Rahayu (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2022)
Mahaputra Senior hight school is one of education institution with goal for give for ability of science and for mastery of technology so that in the next hopelly in society can become generation and skilled, creative, inovativ employed. Goal of community service for giving basic science about finance management with use on line bank system service and making standard operating procedure about online payment.method and solution for problem solving in SMK Mahaputra. Training of community service doing with implemented training as zoom meeting with student, employed and management of SMK Mahaputra with amount 35 participan. Result of community service hoppely can improving management of SMK Mahaputra as increasing number of SOP and using financial digital system. Key words: Bank online, Standard Operating Procedure (SOP)